THE EFFECT OF PROFITABILITY AND COMPANY VALUE ON STOCK RETURNS IN THE INDONESIAN SHARIA STOCK INDEX DURING THE COVID-19 PANDEMIC - Mutia Sumarni; Sophia Rahmah; Chahayu Astina (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2023)
THE EFFECT OF PROFITABILITY AND COMPANY VALUE ON STOCK RETURNS IN THE INDONESIAN SHARIA STOCK INDEX DURING THE COVID-19 PANDEMIC Abstract Purpose: This study aims to analyze the influence of return on assets (ROA) and price book value (PBV) on stock returns of companies listed in the Indonesian Sharia Stock Index during the COVID-19 pandemic. Design/methodology/approach: The research focuses on five companies within the Indonesian Sharia Stock Index, observed from 2019 to 2021. Panel data regression is employed, specifically using the fixed effect model with individual components to estimate the panel data model suitable for company stock values. Findings: The study reveals a positive and significant impact of return on assets (ROA) on stock returns, indicating that profitability influences stock performance. Additionally, price book value (PBV) is found to be significant in affecting stock returns. Research limitations/implications: The research is limited to the selected companies in the Indonesian Sharia Stock Index, and results may vary with different companies or industries. The study period covers the years 2019 to 2021, and subsequent developments may alter the dynamics of the relationships explored. Practical implications: The findings suggest that investors and financial analysts should consider both profitability (ROA) and price book value (PBV) when evaluating the potential returns of companies listed in the Indonesian Sharia Stock Index, particularly during the COVID-19 pandemic. Keywords: Fixed Effect Model, Return on Assets, Price Book Value, Stock Return, Indonesian Sharia Stock Index. PENGARUH PROFITABILITAS DAN NILAI PERUSAHAAN TERHADAP RETURN SAHAM DALAM INDEKS SAHAM SYARIAH INDONESIA SELAMA PANDEMI COVID-19 Abstrak Tujuan: Penelitian ini bertujuan untuk menganalisis pengaruh return on asset (ROA) dan price book value (PBV) terhadap return saham perusahaan yang tercatat dalam Indeks Saham Syariah Indonesia selama pandemi COVID-19. Desain/metodologi/pendekatan: Penelitian ini berfokus pada lima perusahaan dalam Indeks Saham Syariah Indonesia, yang diamati dari 2019 hingga 2021. Regresi data panel digunakan, khususnya menggunakan model efek tetap dengan komponen individual untuk memperkirakan model data panel yang sesuai dengan nilai saham perusahaan. Temuan: Studi ini mengungkapkan dampak positif dan signifikan dari pengembalian aset (ROA) terhadap pengembalian saham, menunjukkan bahwa profitabilitas mempengaruhi kinerja saham. Selain itu, nilai price book (PBV) ditemukan signifikan dalam mempengaruhi pengembalian saham. Keterbatasan / implikasi penelitian: Penelitian ini terbatas pada perusahaan yang dipilih dalam Indeks Saham Syariah Indonesia, dan hasilnya dapat bervariasi dengan perusahaan atau industri yang berbeda. Periode studi mencakup tahun 2019 hingga 2021, dan perkembangan selanjutnya dapat mengubah dinamika hubungan yang dieksplorasi. Implikasi praktis: Temuan menunjukkan bahwa investor dan analis keuangan harus mempertimbangkan profitabilitas (ROA) dan nilai buku harga (PBV) ketika mengevaluasi potensi pengembalian perusahaan yang terdaftar dalam Indeks Saham Syariah Indonesia, terutama selama pandemi COVID-19. Kata kunci: Fixed Effect Model, Return on Assets, Price Book Value, Stock Return, Indeks Saham Syariah Indonesia.